Advanced paternal and grandpaternal age and schizophrenia: A three-generation perspective - Frans, Emma M. (2011)
BACKGROUND: Advanced paternal age has been linked with neurodevelopmental disorders such as schizophrenia. If age-related de novo mutations in the male germ line underlie this association, it would be expected that grandpaternal as well as paternal age may influence the risk of schizophrenia. The aim of the current study was to explore the links between both paternal and grandpaternal age with respect to the risk of schizophrenia in a large, national register-based sample. METHOD: The study was based on Swedish Multi-Generation and Hospital Discharge Registers. Parents’ ages at offspring birth were compared between 20,582 affected and 100,176 non-affected individuals. Grandparents’ ages at the birth of the parent were compared between 2,511 affected and 15,619 non-affected individuals. The risk of schizophrenia was examined when the predictor variable (parent or grandparent age) was examined in age strata with logistic regression. Planned sensitivity analyses included exploring the variables of interest in males and females separately. RESULTS: After adjusting for maternal age, birth year and sex of the proband, we confirmed that the offspring of older fathers have an increased risk of schizophrenia (e.g. compared to paternal age 20–24 years, those with fathers > 55 years had a two-fold increased risk). With respect to grandparent age, older maternal (but not paternal) grandfather age was associated with an increased risk of schizophrenia. Compared to maternal grandfather age 20–24 years, those with maternal grandfathers >55 years had a significantly increased risk of schizohrpenia (Adjusted Odds ratio and 95% Confidence intervals; 2.79, 1.71 – 4.56). The pattern of findings were essentially unchanged when we examine male and female probands separately. CONCLUSION: This is the first the study to show an association between grandpaternal age and risk of schizophrenia. The selective effect of advanced maternal grandfather age suggests that the biological mechanisms involving the X chromosome may differentially contribute to the association between paternal age and risk of schizophrenia.